2022
DOI: 10.3389/fphar.2022.940574
|View full text |Cite
|
Sign up to set email alerts
|

Rhein ameliorates transverse aortic constriction-induced cardiac hypertrophy via regulating STAT3 and p38 MAPK signaling pathways

Abstract: The progression from compensatory hypertrophy to heart failure is difficult to reverse, in part due to extracellular matrix fibrosis and continuous activation of abnormal signaling pathways. Although the anthraquinone rhein has been examined for its many biological properties, it is not clear whether it has therapeutic value in the treatment of cardiac hypertrophy and heart failure. In this study, we report for the first time that rhein can ameliorate transverse aortic constriction (TAC)-induced cardiac hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(39 reference statements)
1
0
0
Order By: Relevance
“…[ 51 ] Our previous study reported that STAT3 may be associated with the polarization of microglia in RIR injury and that rhein can inhibit the activation of the STAT3 signaling pathway; however, the ability of rhein to regulate the STAT3 signaling pathway in RIR injury has not been reported. [ 9 , 24 , 52 ] Our in vitro and in vivo results show that Rh‐GFFYE can inhibit the phosphorylation of STAT3 protein, which is similar to our previous report on the mechanism of action of ginsenoside Rg3 liposomes in RIR injury. [ 9a ] These results provide a rationale for the regulation of microglia polarization by the natural product rhein.…”
Section: Discussionsupporting
confidence: 89%
“…[ 51 ] Our previous study reported that STAT3 may be associated with the polarization of microglia in RIR injury and that rhein can inhibit the activation of the STAT3 signaling pathway; however, the ability of rhein to regulate the STAT3 signaling pathway in RIR injury has not been reported. [ 9 , 24 , 52 ] Our in vitro and in vivo results show that Rh‐GFFYE can inhibit the phosphorylation of STAT3 protein, which is similar to our previous report on the mechanism of action of ginsenoside Rg3 liposomes in RIR injury. [ 9a ] These results provide a rationale for the regulation of microglia polarization by the natural product rhein.…”
Section: Discussionsupporting
confidence: 89%